Thread Pitch Test of Candlenut Oil Press Screw - Josafat Simanjuntak; Saipul Bahri Daulay; Ainun Rohanah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Basicly, the oil press is designed for pressing the candlenut. This reasearch was on testing of thread pitch variaton of oil press which was aimed to measure the best thread pitch of candlenut oil press. This reasearch was conducted at agriculture engineering laboratory USU on August 2014 – January 2015 using non factorial randomized block design with three grades, i . e 1 cm, 2,5 cm, and 4 cm. Parameters observed were effective capacity, losses, and yield. The best grade for effective capacity and yield was P3 (pitch 4 cm) which produced 0,381 l/kg and 322 l/kg; and the best grade for losses was P2 (2,5 cm) which produced 29,733 % Keyword: pressing, candlenut, candlenut oil, thread